China and Malaysia in a globalizing world bilateral relations, regional imperatives and domestic challenges - Yeoh, Emile Kok-Kheng; Hou, Kok Chung 1963- (Institute of China Studies, University of Malaya, 2006)
The research papers collected in this volume cover the critical aspects of the issue from various different perspectives, ranging from China's changing political and economic relations with Malaysia and Southeast Asia to the impact of her WTO membership on the regional economy, from the thorny issue of nationality and citizenship -- in particular related to the 'new Chinese migrants' -- to China's domestic challenges engendered by the country's "retreat from equality", growing interregional disparity, increased local autonomy, rapid economic growth and increasingly globalizing trade and business linkages.